2018
DOI: 10.1021/acs.orglett.8b01520
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonamide Synthesis via Calcium Triflimide Activation of Sulfonyl Fluorides

Abstract: A method using calcium triflimide [Ca(NTf)] as a Lewis acid to activate sulfonyl fluorides toward nucleophilic addition with amines is described. The reaction converts a wide array of sterically and electronically diverse sulfonyl fluorides and amines into the corresponding sulfonamides in good yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 31 publications
(22 reference statements)
0
58
0
Order By: Relevance
“…It was found that 10b did not react with benzylamine even at elevated temperatures (80 °C). Nonetheless, the reaction occurred upon catalysis with Ca(NTf) 2 (a procedure described recently by Pfizer chemists) to give the product 15b (27 % yield); partial removal of the tert ‐butyl protective group was observed according to 1 H NMR and LC‐MS. Analogously, sulfonyl fluoride 10c gave the target sulfonamide 15c (44 % yield); the carbamate moiety remained intact under the conditions used.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that 10b did not react with benzylamine even at elevated temperatures (80 °C). Nonetheless, the reaction occurred upon catalysis with Ca(NTf) 2 (a procedure described recently by Pfizer chemists) to give the product 15b (27 % yield); partial removal of the tert ‐butyl protective group was observed according to 1 H NMR and LC‐MS. Analogously, sulfonyl fluoride 10c gave the target sulfonamide 15c (44 % yield); the carbamate moiety remained intact under the conditions used.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Scheme , nucleophilic substitution at sulfur was achieved through the reaction of alkenylsulfonyl fluoride 5 b with p ‐methoxyphenol to form sulfonate ester 6 in 84 % yield, or with pyrrolidine to form sulfonamide 7 in 51 % yield. With the aid of stoichiometric Ca(NTf 2 ) 2 as a Lewis acid, anilines could also be used as nucleophiles to form alkenyl sulfonamides 8 a and 8 b in good yields. Alternatively, softer sulfur nucleophiles such as thiols and thiophenols underwent base‐catalyzed conjugate addition to the electron‐poor alkene in quantitative yields ( 9 a – c ).…”
Section: Methodsmentioning
confidence: 99%
“…A facile synthesis of sulfonamides is necessary to produce a variety of compounds with the potential to improve human health. A review of the current literature suggests that nucleophilic substitution of sulfonyl halides or sulfonic acids with an amine is an efficient method for the synthesis of sulfonamides (Mukherjee et al, 2018;De Luca & Giacomelli, 2008). The title compound was synthesized by reacting ptoluenesulfonyl chloride with propylamine in the presence of pyridine.…”
Section: Chemical Contextmentioning
confidence: 99%